2014
DOI: 10.1097/qai.0b013e3182a39979
|View full text |Cite
|
Sign up to set email alerts
|

Immunodeficiency at the Start of Combination Antiretroviral Therapy in Low-, Middle-, and High-Income Countries

Abstract: Objectives To describe the CD4 cell count at the start of combination antiretroviral therapy (cART) in low-income (LIC), lower middle-income (LMIC), upper middle-income (UMIC) and high-income (HIC) countries. Methods Patients aged ≥16 years starting cART in a clinic participating in a multi-cohort collaboration spanning six continents (International epidemiological Databases to Evaluate AIDS and ART Cohort Collaboration) were eligible. Multi-level linear regression models were adjusted for age, gender and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
77
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(80 citation statements)
references
References 29 publications
(32 reference statements)
2
77
1
Order By: Relevance
“…Surprisingly, although this was an analysis of specific HIV sites in an urban setting, our reported median CD4 + cell count at ART initiation reached up to 293 cells/µl in 2011, and is considerably higher than the recent estimates of median CD4 + of 155 cells/µl in 2009 from clinical sites in various LMICs [18]. Therefore, our observation of higher median CD4 + cell count at ART initiation is different from the consistently reported low median CD4 + cell count at ART initiation in other SSA settings [3,4,710].…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Surprisingly, although this was an analysis of specific HIV sites in an urban setting, our reported median CD4 + cell count at ART initiation reached up to 293 cells/µl in 2011, and is considerably higher than the recent estimates of median CD4 + of 155 cells/µl in 2009 from clinical sites in various LMICs [18]. Therefore, our observation of higher median CD4 + cell count at ART initiation is different from the consistently reported low median CD4 + cell count at ART initiation in other SSA settings [3,4,710].…”
Section: Discussioncontrasting
confidence: 82%
“…The median CD4 + cell count at ART initiation in our study of HIV-infected Rwandan patients is higher than reported in other studies in the region [10,15,16]. A global analysis of data from 48 countries, including those in North America, Europe, and SSA, found that in 2009 the United States had the highest mean CD4 + cell count at ART initiation (307 cells/µl) followed, remarkably, by Rwanda (287 cells/µl) [17,18]. Given this and other HIV programmatic scale-up successes in Rwanda [13,14,19], there are likely important lessons to be learned by comparing Rwanda’s experience with those of other countries in SSA.…”
Section: Discussionmentioning
confidence: 48%
“…Despite concrete evidence that HIV infection should be treated upon diagnosis even at CD4 T cell counts above 500 cells/μL [7], the sobering reality is that many patients present late at diagnosis or treatment initiation in both resource limited and resource rich settings [8]. According to US statistics, 23% of patients get diagnosed with HIV at stage 3 (AIDS) [9] and recent studies from South Africa [10] and Europe [11] report similar statistics with a persistently high proportion of patients presenting late for therapy initiation.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality in the first year on ART was as high as 40%, with the majority of deaths occurring in the first three months after ART initiation [35]. Patients with the lowest CD4 T-cell counts have the highest mortality risk [511], and despite expanded voluntary HIV counseling and testing efforts, many patients still present with advanced immunosuppression [1215]. …”
Section: Introductionmentioning
confidence: 99%